2013
DOI: 10.5747/cv.2013.v005.n1.v072
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Epidemiológico Da Anemia Ferropriva No Serviço De Hematologia De Um Hospital Público, Estado De São Paulo, Brasil

Abstract: A anemia ferropriva possui diversas etiologias, como nutricional, absortivas, metabólicas ou distributivas, sangramento e aumento das necessidades fisiológicas. Apesar do impacto epidemiológico e clínico, a anemia ainda permanece incerta quanto à epidemiologia, principalmente pela falta de dados consistentes em nossa região. O objetivo deste estudo foi determinar o perfil epidemiológico dos pacientes atendidos pelo serviço de hematologia de um hospital público do estado de São Paulo no período de 2005 a 2010, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…For these variables, income alone was significantly different between the areas surveyed, which can be attributed to the higher proportion of people who reported income below a minimum wage in scenario B, when compared to A. These characteristics corroborate with other studies developed in the national context (7)(8)(9)(10) , revealing characteristics inherent to lower socioeconomic strata in patients from services funded by the Unified Health System.…”
Section: Discussionsupporting
confidence: 85%
“…For these variables, income alone was significantly different between the areas surveyed, which can be attributed to the higher proportion of people who reported income below a minimum wage in scenario B, when compared to A. These characteristics corroborate with other studies developed in the national context (7)(8)(9)(10) , revealing characteristics inherent to lower socioeconomic strata in patients from services funded by the Unified Health System.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the most common etiology, iron deficiency affected 62.7% of patients. Souza et al 15 also found menstrual bleeding in women as the main cause of anemia, and gastrointestinal bleeding in the elderly, as in this study. As it is a private service, nutritional deficiency (17.1% of our cases of iron deficiency anemia) was not more prevalent than bleeding, as in other studies carried out in Brazil 1 .…”
Section: Discussionsupporting
confidence: 84%
“…Also according to the WHO, anemia is defined as "low hemoglobin concentration" 8,10,11,13,14 . The causes for this situation vary, such as: nutritional deficiencies, blood loss, early destruction of red blood cells in the bloodstream, inflammatory diseases and renal failure 4,7,10,11,15,16 . The WHO criteria for diagnosing anemia is hemoglobin below 13 g/ dL in men and below 12 g/dL in women 1,6,11,14,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to the age group, the one that presented the highest number of individuals who tested positive were between 0-11 years. This same age group has been shown to be the most infected in other studies (ARAÚJO-FILHO et al, 2011;SOUZA et al, 2013). However, the above mentioned studies presented discordant results to Santos, Santos and Soares (2007) that observed that as the age increases, there is a progressive growth of frequency of parasitic infections.…”
Section: Resultsmentioning
confidence: 52%